Primary Prevention Implantable Cardioverter Defibrillator (ICD) Therapy in Women—Data From a Multicenter French Registry. Issue 2 (February 2016) - Providência, Rui; Marijon, Eloi; Lambiase, Pier D.; Bouzeman, Abdeslam; Defaye, Pascal; Klug, Didier; Amet, Denis; Perier, Marie‐Cécile; Gras, Daniel; Algalarrondo, Vincent; Deharo, Jean‐Claude; Leclercq, Christophe; et al.
Abstract : Background: There are limited data describing sex specificities regarding implantable cardioverter defibrillators (ICDs) in the real‐world European setting. Methods and Results: Using a large multicenter cohort of consecutive patients referred for ICD implantation for primary prevention (2002–2012), in ischemic and nonischemic cardiomyopathy, we examined the sex differences in subjects' characteristics and outcomes. Of 5539 patients, only 837 (15.1%) were women and 53.8% received cardiac resynchronization therapy. Compared to men, women presented a significantly higher proportion of nonischemic cardiomyopathy (60.2% versus 36.2%, P <0.001), wider QRS complex width (QRS >120 ms: 74.6% versus 68.5%, P =0.003), higher New York Heart Association functional class (≥III in 54.2%♀ versus 47.8%♂, P =0.014), and lower prevalence of atrial fibrillation (18.7% versus 24.9%, P <0.001). During a 16 786 patient‐years follow‐up, overall, fewer appropriate therapies were observed in women (hazard ratio=0.59, 95% CI 0.45–0.76; P <0.001). By contrast, no sex‐specific interaction was observed for inappropriate shocks (odds ratio ♀=0.84, 95% CI 0.50–1.39, P =0.492), early complications (odds ratio=1.00, 95% CI 0.75–1.32, P =0.992), and all‐cause mortality (hazard ratio=0.87 95% CI 0.66–1.15, P =0.324). Analysis of sex‐by‐ cardiac resynchronization therapy interaction shows than female cardiac resynchronization therapy recipients experienced fewer appropriate therapies than men (hazard ratio=0.62, 95% CI 0.50–0.77; P <0.001) and lower mortality (hazard ratio=0.68, 95% CI 0.47–0.97; P =0.034). Conclusions: In our real‐life registry, women account for the minority of ICD recipients and presented with a different clinical profile. Whereas female cardiac resynchronization therapy recipients had a lower incidence of appropriate ICD therapies and all‐cause death than their male counterparts, the observed rates of inappropriate shocks and early complications in all ICD recipients were comparable. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT01992458.